PELATIHAN PEMBUATAN ABON BAHAN DASAR IKAN GASTOR BAGI MASYARAKAT KAMPUNG TORAY DISTRIK SOTA - M Loupatty; I H Wayangkau (Musamus University, 2019)
Gastor is one type of fish contain nutritional value namely protein. Gastor is captured traditionally by the Toray village community. Meanwhile, Gastor is unmanaged as it is only for consumptive need. Based on the fish characteristic, Gastor can be processed to increase its values thus training for manufacturing is needed. Training is arranged systematically in order to implement the program perfectly. Training program following this sequence namely preparation stage, implementation stage and evaluation stage. In addition, fresh Gastor fish caught by the Toray village community is the main material accompanied by other ingredients to formulate Abon Gastor. The training participants to create Abon Gastor include six housewife, four teenager, and two village officials. Product flavor can be adjusted to be meet local as well as national needs. Based on the result, 1 kg of Gastor fish can produce ± 2 ounces Abon Gastor. The aim of the training is expected that the community is able to have skills in processing fishery products that can improve the welfare and independence of the community in Toray village.